EPIZOOTOLOGIC AND DIAGNOSTIC OF TOKSOPLASMOSIS OF GOATS - Березовський, А. В.; Галат, М. В.; Небещук, Л. В.; Рибальченко, Д. Ю. (Scientific Progress & Innovations, 2013)
The paper presents data about the using of different test kits for in vivo diagnostics of toxoplasmosis of goats. The peculiarities of the course of invasion are established, which depends on the season of the year, as well as age, sex and breed of animals. An infection of sapling of goats from one year was 10 %, at the same time as at animals by age from five to six years this index was increased and evened 30 %. Maximal staggered it was registered toxoplasmes at animal regional breeds. Extensiveness of invasion among the females of goats was considerably higher (72,2 %) as compared to males (20 %).